Restructuring and Regional Policy in Hungary - Horváth, Gyula; Hrubi, László (Discussion Papers, 1992)
The present study focuses on structural changes in depressed areas taking as an example the region around the towns Pécs and Komló. The problem of depressed areas viewed as an issue of regional policy is relatively new in Hungary. This is the reason why the authors extend their analysis well beyond the actual problems of the Pécs-Komló region and raise more general questions related to structural changes at regional level. After a general presentation of the signs of depression in the urban area of Pécs, the authors present new forces driving the development of the area and the adjustment strategy of the region based on innovation and the development of local culture. The final sections deal with the changing role of local developments and the changing function of regional development.